Optoelectronic Switches: An Optoelectronic Switch Based on Intrinsic Dual Schottky Diodes in Ambipolar MoSe2 Field‐Effect Transistors (Adv. Electron. Mater. 11/2015). (18th November 2015) - Pradhan, Nihar R.; Lu, Zhengguang; Rhodes, Daniel; Smirnov, Dmitry; Manousakis, Efstratios; Balicas, Luis
Abstract : In article number 1500215, Nihar R. Pradhan, Luis Balicas, and co‐workers demonstrate that the Schottky barriers between metallic interconnects and a van der Waals coupled semiconductor can lead to a light‐induced, diode‐like response with a sense of current rectification that can be controlled via a back gate voltage. This effect corresponds to a novel type of optoelectronic switch, with potential for technological applications. The image depicts the underlying process, including electron‐hole pair generation, the modulation of the Schottky barrier, and control of the electrical current.